Book Review: Ruby R. Brougham (Ed.). 2009. New Directions in Aging Research: Health and Cognition. Issue 2 (December 2017) - Srivastava, Shashi Kant
Ruby R. Brougham (Ed.). 2009. New Directions in Aging Research: Health and Cognition . New York: Nova Biomedical Books, 200 pp., £41.73, ISBN 978-1-61728-547-9